Three new species of the family Cirolanidae Dana, 1852 (Isopoda, Cymothoida) from the shallow Brazilian bathyal - Paiva, Ricardo J. C.; Souza-Filho, Jesser F. (Zootaxa, 2023)
Three new species of isopod crustaceans of the family Cirolanidae—Dolicholana ivanyae spec. nov., Natatolana hadassae spec. nov. and Politolana cleoniceae spec. nov.—are described from the shallow waters of the Brazilian bathyal. The specimens were collected from the shallow bathyal zone of the Potiguar Basin, off the Brazilian state of Rio Grande do Norte, from Pernambuco and Bahia, and the Campos Basin, off Rio de Janeiro and São Paulo states. Dolicholana ivanyae spec. nov. can be distinguished from its congeners by the subrectangular shape of the head, its very long frontal lamina, which surpasses article 2 of the peduncle of antenna 1, and its densely setose pereopod 7. Natatolana hadassae spec. nov. is unique due to the subacute posteroventral angle of epimeron 4, ischial pereopod 3 as produced as those of pereopods 1 and 2, and the distal margin of the pleotelson with 10 robust distal setae. Politolana cleoniceae spec. nov. differs from its congeners based on the combination of the following traits: the pereon-pleon articulation is tight, with pleonite 1 clearly visible, and not covered completely by pereonite 7, while the pleon (in the dorsal-ventral view) is arched in a uniform sequence with the pereon, and the uropodal endopod is shorter than the exopod. In addition to these findings, the known geographical distribution of Dolicholana brucei, which was described recently from Brazil, is extended southward to include Bahia, Brazil. This study increases the number of cirolanid species recorded from Brazilian waters to 23.